2019
DOI: 10.1515/chem-2019-0092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant activity of 2-methylthio-pyrido[3,2-e][1,2,4] triazolo[1,5-a]pyrimidines

Abstract: A series of 2-methylthio-pyrido-triazolopyrimidines (1-17) were prepared by the reaction of dimethyl-N-cyanoimidodithiocarbonate with hydrazinopyridine carboxylic acid as starting reactants. Their chemical structures were affirmed with HREI-MS, IR and NMR analyses. The target compounds (1-17) were evaluated for their antioxidant activity using 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging, ferric reduction antioxidant power (FRAP) and reducing power capability (RPC). The results revealed that some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Throughout our research, we have noticed that the 1,2,4-triazole or 1,2,3-triazole derivatives showed antioxidant properties [28][29][30][31][32][33][34][35] and demonstrated cytotoxic activity as well. In a previous work, the molecular hybridization technique was employed to incorporate the triazole unit with isothiocyanate and substituted benzylidene groups into a single molecule; the resulting targets have the potential to exhibit potent antiproliferative activity against HCT-116 and MCF-7 human cancer cell lines and showed very weak cytotoxicity against normal cells [35].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Throughout our research, we have noticed that the 1,2,4-triazole or 1,2,3-triazole derivatives showed antioxidant properties [28][29][30][31][32][33][34][35] and demonstrated cytotoxic activity as well. In a previous work, the molecular hybridization technique was employed to incorporate the triazole unit with isothiocyanate and substituted benzylidene groups into a single molecule; the resulting targets have the potential to exhibit potent antiproliferative activity against HCT-116 and MCF-7 human cancer cell lines and showed very weak cytotoxicity against normal cells [35].…”
Section: Introductionmentioning
confidence: 79%
“…The Schiff bases of 4-aminotriazole derivatives demonstrated potential free radical scavenger effects, whereas the N-substituted triazole attached indole/chalcone hybrids and 1,2,4-triazole-3-thiones reported to exhibit significant antioxidant activity on DPPH radicals and were found to be potent anticancer agents [30,31]. Incorporation of 1,2,4-triazole ring with quinazoline and pyridopyrimidine units was proved to be favorable for the antioxidant and cytotoxicity activities [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic methodology for target pyridotriazolopyrimidines ( Table 1 and Scheme 1) has been previously described [10,11]. As illustrated in Table 2, the in vitro cytotoxicity of pyridotriazolopyrimidines was evaluated against A549, HepG2, MCF-7, and WRL 68 cells using the MTT assay.…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%
“…For HepG2, IP has the strongest effect with a regression coefficient of 13.34. For MCF-7, the electronegativity displays the strongest contribution with a moderate effect on electrophilicity contribution (equation (11)). Hardness (with a negative contribution of 8.70) shows the strongest effect on the activity of the tested compounds against WRL68 (equation (12)).…”
Section: Considering Subclasses 2a and 2c-2fmentioning
confidence: 99%
See 1 more Smart Citation